Predicting state police officer alcohol consumption and use of tobacco - Copenhaver, Allen (International journal of police science & management, 2018)
Criminal justice research has well documented the fact that law enforcement officers experience a significant amount of stress. Research also suggests law enforcement officers use tobacco (which is not healthy at any rate) and alcohol at rates exceeding those of other populations. Although several studies have documented the above across a wide variety of law enforcement populations, research has not previously explored the extent to which state police officers use tobacco and alcohol. Because no studies explore state law enforcement officer use of tobacco and alcohol, no studies exist that identify factors predictive of state police officer use of alcohol and tobacco. This study addresses these gaps in the literature by surveying all sworn state police officers of one state police agency. Policy recommendations, as they pertain to reducing state police officer use of alcohol and tobacco are discussed below.